Access to Justice and Legal Empowerment : A Review of World Bank Practice - Maru, Vivek (World Bank, Washington, DC, 2014)
This paper reviews the World Bank's existing work in access to justice and suggests directions for further Bank engagement in this area. Accesses to justice efforts are grouped here into six categories: court reforms, legal aid, information dissemination and education, alternative dispute resolution, public sector accountability, and research. The paper is motivated in part by recent discussions of 'legal empowerment;' a thread of inquiry that runs through the review is: how do World Bank efforts to increase access to justice affect the agency of poor people? The paper concludes with insights and recommendations that emerge from the Bank's experience. All justice reform interventions should attend to particularities of sociolegal context, should consider the specific justice needs of poor people, and should be planned not in isolation, but from a system wide perspective. Legal services and legal aid interventions should confront the challenge of scale, should consider alternative methods of service delivery, and should in some cases take care to maintain at least partial independence from the state. The use of non-court dispute resolution mechanisms should be guided by the benefits achieved in cost, time, harmony, and fairness. Evaluations of access to justice programs should go beyond 'headcounts' to demonstrate impact on users of justice services as well as on society at large and to weigh opportunity cost.